2020
DOI: 10.1007/s10995-019-02865-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Anemia Status Among Children Aged 6–59 months in Ghana, 2003–2014

Abstract: Background In 2008, 78% of Ghanaian children under 5 years old were anemic versus 48% of children globally. In this study, we identified proximal and distal determinants of severe-moderate anemia and mild anemia related to socioeconomic status, nutrition, and health access. Methods Using data from the 2003, 2008, and 2014 Ghana Demographic and Health Surveys (GDHS), the odds of severemoderate anemia and mild anemia compared to no anemia, in relation to various hypothesized risk factors, were assessed using a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
30
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 30 publications
10
30
0
9
Order By: Relevance
“…Our study found that a higher level of maternal education and residence in economically developed areas were associated with lower odds of developing anaemia. This observation is in concordance with findings from Ghana [ 21 ], Guinea [ 22 ], India [ 23 , 24 ] and other studies in China [ 25 ]. Although the socioeconomic indicators for China (e.g., food expenditure, average disposable income and gross domestic product per capita) have increased in both urban and rural areas over the past decades [ 26 , 27 ], holistic socioeconomic conditions remain better in urban and Eastern/Central areas than in rural and Western areas [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that a higher level of maternal education and residence in economically developed areas were associated with lower odds of developing anaemia. This observation is in concordance with findings from Ghana [ 21 ], Guinea [ 22 ], India [ 23 , 24 ] and other studies in China [ 25 ]. Although the socioeconomic indicators for China (e.g., food expenditure, average disposable income and gross domestic product per capita) have increased in both urban and rural areas over the past decades [ 26 , 27 ], holistic socioeconomic conditions remain better in urban and Eastern/Central areas than in rural and Western areas [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the prevalence of anemia among children aged 6-59 months in Ethiopia was 57.56% (95%CI: 56.50%, 58.61%) ranged from 42.66% in the Amhara region to 83.24% in the Somali region. This was higher than a study reported in Ghana [41] and China [42]. Even though the combined strategies particularly iron supplementation and infectious disease management (such as malaria and helminths infections) are being introduced by the WHO to combat anemia, anemia remains a serious health care problem in Ethiopia.…”
Section: Discussionmentioning
confidence: 67%
“…A large study in Ghana involving 2123 children conducted around the same period as the current study found anaemia and malaria prevalence of 35.6% and 20.3%, respectively, in children under 5 years [ 25 ]. An earlier household survey of 7739 children under 5 years in 2014 also found 40% anaemia prevalence [ 26 ]. About 3 years later, where several conditions contributing to anaemia in the country should have been better, anaemia prevalence of over 60% would not have been expected—and is strongly associated with malaria in this study and owing to artisanal mining in these sites.…”
Section: Discussionmentioning
confidence: 99%